Neutron reflectometry with the Multi-Blade 10B-based detector. (22nd August 2018) - Mauri, G.; Messi, F.; Anastasopoulos, M.; Arnold, T.; Glavic, A.; Höglund, C.; Ilves, T.; Lopez Higuera, I.; Pazmandi, P.; Raspino, D.; Robinson, L.; Schmidt, S.; et al.
Abstract : The Multi-Blade is a boron-10-based gaseous detector developed for neutron reflectometry instruments at the European Spallation Source in Sweden. The main challenges for neutron reflectometry detectors are the instantaneous counting rate and spatial resolution. The Multi-Blade has been tested on the CRISP reflectometer at the ISIS Neutron and Muon Source in the UK. A campaign of scientific measurements has been performed to study the Multi-Blade response in real instrumental conditions. The results of these tests are discussed in this paper.